2022
DOI: 10.1038/s41598-022-07600-x
|View full text |Cite
|
Sign up to set email alerts
|

Deprogramming metabolism in pancreatic cancer with a bi-functional GPR55 inhibitor and biased β2 adrenergic agonist

Abstract: Metabolic reprogramming contributes to oncogenesis, tumor growth, and treatment resistance in pancreatic ductal adenocarcinoma (PDAC). Here we report the effects of (R,S′)-4′-methoxy-1-naphthylfenoterol (MNF), a GPR55 antagonist and biased β2-adrenergic receptor (β2-AR) agonist on cellular signaling implicated in proliferation and metabolism in PDAC cells. The relative contribution of GPR55 and β2-AR in (R,S′)-MNF signaling was explored further in PANC-1 cells. Moreover, the effect of (R,S′)-MNF on tumor growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…A recent study revealed that ADRB2 agonists downregulated the MYC pathway and HIF-1A, inducing specific metabolic reprogramming in PDAC (40). These reprogramming include the upregulation of glycolytic metabolism and changes in acylcarnitine levels (40), ultimately leading to the suppression of PDAC progression. These findings parallel our observations regarding ADRA2A in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that ADRB2 agonists downregulated the MYC pathway and HIF-1A, inducing specific metabolic reprogramming in PDAC (40). These reprogramming include the upregulation of glycolytic metabolism and changes in acylcarnitine levels (40), ultimately leading to the suppression of PDAC progression. These findings parallel our observations regarding ADRA2A in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenoceptor beta 2 (ADRB2) is a member of adrenergic receptor family, sharing similar functions with ADRA2A. A recent study revealed that ADRB2 agonists downregulated the MYC pathway and HIF-1A, inducing specific metabolic reprogramming in PDAC (40). These reprogramming include the upregulation of glycolytic metabolism and changes in acylcarnitine levels (40), ultimately leading to the suppression of PDAC progression.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Only subsets of patients will progress along the sequence of worsened pathophysiological states from NAFL to NASH and further to cirrhosis, thereby being exposed to an increasing risk for HCC development [ 246 ]. The pathophysiological mechanisms underlying the risk connection between NAFLD and HCC include various components such as immune and inflammatory responses, DNA damage, oxidative stress, changes in the microbiome, and others that go beyond the scope of this review and have been comprehensively summarized elsewhere [ 5 ].…”
Section: Extracellular Matrix Remodeling and Fibrosis Linking Obesity...mentioning
confidence: 99%